THE INFLUENCE OF TRAINING, KNOWLEDGE MANAGEMENT AND JOB SATISFACTION ON INNOVATION PERFORMANCE IN EMPLOYEES OF PERUMDA AIR MINUM TIRTA PROJOTAMANSARI BANTUL DISTRICT - Asmarani, Putri; Chandra Kirana, Kusuma; Hadi, Syamsul (International Conference on Humanity Education and Society (ICHES), 2024)
Abstract Innovation performance is the result of employee creativity in the organization, some literature that can improve innovation performance such as conducting training, knowledge management and job satisfaction in employees. This article aims to determine the effect of Training, Knowledge Management and Job Satisfaction on Innovation Performance. This research was conducted on employees of the Drinking Water Company using quantitative methods, and data collected through questionnaires distributed to a sample of 131 employees. Sampling is done by applying a random sampling method, while data processing uses SPSS Version 23. The results showed that Training, Knowledge Management and Job Satisfaction had a significant positive effect on Innovation Performance.